PROTOTIPE MOBILE STATION UNTUK PEREKAMAN KANDUNGAN UDARA - Bella, Gusti Ketut; Putra Sastra, Nyoman; Diafari Djuni Hartawan, I G. A. K. (Jurnal SPEKTRUM; Vol 5 No 1 (2018): Jurnal SPEKTRUM, 2018)
This study aims to monitor the air quality of Denpasar city with mobile station that can transmit air content information in mobile and real time. This mobile station was built using Wemos D1 Mini Board which is a small wifi board based on ESP8266. Information sent via the Wemos D1 board is information obtained from sensors MQ-7 and MQ-135 and DHT11. DHT11, MQ-7 and MQ-135 sensors can detect the temperature, CO and NH3 gas, NOx, alcohol, benzene, smoke and CO2. Information obtained from the sensors will be posted on a website so that people can know the level of air pollution in the city of Denpasar. This developed monitoring system has successfully displayed data in the form of a folder on the web server.